Author Correction: Herbivorous turtle ants obtain essential nutrients from a conserved nitrogen-recycling gut microbiome - Yi Hu (Nature Portfolio, 2018)
The originally published version of the Supplementary Information file associated with this Article contained an error in Supplementary Figure 3. Panel b was inadvertently replaced with a duplicate of panel a. The error has now been fixed and the corrected version of the Supplementary Information PDF is available to download from the HTML version of the Article.